White Nights - The Army as Immediate Controller of the Barbarism Management - Menegat, Marildo (Geografares, 2019)
The author argues that the military protagonism in the 2018 elections, composing the field activated by the “new right”, has as a background an adaptation to the underway needs of the world order wars as updated modes of managing the capital crisis aggravated since 2008. The proclaimed leadership of the Army is not the beginning of the state of exception, but only a moment of its deepening that will tend to continue in the next period.
Keywords: state of exception; barbarism management; wars of world order